2021
DOI: 10.1111/ijcp.13961
|View full text |Cite
|
Sign up to set email alerts
|

Association between temporomandibular disorders with clinical and sociodemographic features: An observational study

Abstract: The temporomandibular joint (TMJ) is a gliding joint formed by the mandibular condyle, the mandibular fossa of the temporal bone, a ligamentous synovial capsule, an articular disk, and retrodiskal tissue allow for smooth joint movement. 1 This synovial joint showed free nerve endings and different sensory nerve organs regarding the sensorial and proprioceptive innervation by the masseteric and auriculotemporal nerves and contributes to nourish and lubricate avascular surfaces and to protect bacterial infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
1
9
0
2
Order By: Relevance
“…Several studies have demonstrated an association between psychological factors and TMD, with higher depression/anxiety levels found in patients with TMD [ 3 , 8 , 13 , 28 ]. On the other hand, other studies have failed to find any such association [ 29 , 30 ]. In this study, a significant association was found between the presence and severity of symptoms of TMD and signs/symptoms of depression/anxiety.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have demonstrated an association between psychological factors and TMD, with higher depression/anxiety levels found in patients with TMD [ 3 , 8 , 13 , 28 ]. On the other hand, other studies have failed to find any such association [ 29 , 30 ]. In this study, a significant association was found between the presence and severity of symptoms of TMD and signs/symptoms of depression/anxiety.…”
Section: Discussionmentioning
confidence: 92%
“… 249 patients (150W, 99M), not practicing social isolation during COVID-19 pandemic. Delgado-Delgado, 2021 39 (Spain) Observational DC/TMD 59 participants with (n = 45) and without (n = 14) TMD (35 F, 24 M, mean age = 28.0 ± 10.1 years). Tavares, 2021 40 (Brazil) Cross-sectional cohort cut RDC/TMD 15 patients (5 W, 10 M, mean age = 69.0 years), elderly people with Parkinson’s disease associated with TMD and depression.…”
Section: Resultsmentioning
confidence: 99%
“…Trotz reichlich epidemiologischer und experimenteller Studien konnte keine eindeutige kausale Beziehung zwischen Okklusion und CMD festgestellt werden [13][14][15]. So reichen die Meinungen über die Bedeutung der Okklusion bei CMD von Hauptverursacher, bis hin zu fehlender Korrelation überhaupt [16].…”
Section: Diskussionunclassified